Landscape fragmentation constrains bumblebee nutritional ecology and foraging dynamics - E. Pioltelli; L. Guzzetti; M. Ouled Larbi; M. Labra; A. Galimberti; P. Biella (Landscape and Urban Planning, 2024)

A global analysis of field body temperatures of active squamates in relation to climate and behaviour - Shahar Dubiner; Rocío Aguilar; Rodolfo O. Anderson; Diego M. Arenas Moreno; Luciano J. Avila; Estefania Boada‐Viteri; Martin Castillo; David G. Chapple; Christian O. Chukwuka; Alison Cree; Félix B. Cruz; Guarino R. Colli; et al. (Global Ecology and Biogeography, 2024)
Aim Squamate fitness is affected by body temperature, which in turn is influenced by environmental temperatures and, in many species, by exposure to solar radiation. The biophysical drivers of body temperature have been widely studied, but we lack an integrative synthesis of actual body temperatures experienced in the field, and their relationships to environmental temperatures, across phylogeny, behaviour and climate. Location Global (25 countries on six continents). Taxa Squamates (210 species, representing 25 families). Methods We measured the body temperatures of 20,231 individuals of squamates in the field while they were active. We examined how body temperatures vary with substrate and air temperatures across taxa, climates and behaviours (basking and diel activity). Results Heliothermic lizards had the highest body temperatures. Their body temperatures were the most weakly correlated with substrate and air temperatures. Body temperatures of non‐heliothermic diurnal lizards were similar to heliotherms in relation to air temperature, but similar to nocturnal species in relation to substrate temperatures. The correlation of body temperature with air and substrate temperatures was stronger in diurnal snakes and non‐heliothermic lizards than in heliotherms. Body‐substrate and body‐air temperature correlations varied with mean annual temperatures in all diurnal squamates, especially in heliotherms. Thermal relations vary with behaviour (heliothermy, nocturnality) in cold climates but converge towards the same relation in warm climates. Non‐heliotherms and nocturnal species body temperatures are better explained by substrate temperature than by air temperature. Body temperature distributions become left‐skewed in warmer‐bodied species, especially in colder climates. Main Conclusions Squamate body temperatures, their frequency distributions and their relation to environmental temperature, are globally influenced by behavioural and climatic factors. For all temperatures and climates, heliothermic species' body temperatures are consistently higher and more stable than in other species, but in regions with warmer climate these differences become less pronounced. A comparable variation was found in non‐heliotherms, but in not nocturnal species whose body temperatures were similar to air and substrate irrespective of the macroclimatic context.

Does Liolaemus lemniscatus eavesdrop on the distress calls of the sympatric weeping lizard? - Lydia J. M. Fong; Fernando Navea; Antonieta Labra (Journal of Ethology, 2021)
For a prey, its best ticket to stay alive is to get early and accurate information on predation risk and so, escape from predation at low cost. Some prey species have evolved the ability to eavesdrop signals intended for others, which contain information on predation risk. This is the case for the vocalizations produced by prey species when interacting with predators. Although primarily studied in birds and mammals, eavesdropping on vocal signals has been recorded in some lizard species. Here, we explored whether the lizard Liolaemus lemniscatus eavesdrops on the distress calls of its sympatric species, the Weeping lizard ( L. chiliensis ). Individuals of the Weeping lizard respond to these calls by displaying antipredator behaviours (i.e., reduced movement), and individuals of L. lemniscatus may potentially display similar defences if they decode the information contained in these calls. Our playback experiments showed that individuals of L. lemniscatus responded to the sound stimuli (distress calls and white noise), reducing their activity, but they did not discriminate between these two stimuli, suggesting that L. lemniscatus does not eavesdrop on the distress calls of its sympatric lizard species. We discuss some hypotheses to explain the lack of eavesdropping by L. lemniscatus on the Weeping lizard distress calls.

The Importance of Intraspecific Variation for Niche Differentiation and Species Distribution Models: The Ecologically Diverse Frog Pleurodema thaul as Study Case - Aura M. Barria; Daniel Zamorano; Andrés Parada; Fabio A. Labra; Sergio A. Estay; Leonardo D. Bacigalupe (Evolutionary Biology, 2020)

The role of arrival time to the breeding grounds in the song development of juvenile pied flycatchers - Lydia J. M. Fong; Antonieta Labra; Helene M. Lampe (Journal of Ethology, 2019)

A framework based on sulcal constraints to align preterm, infant and adult human brain images acquired in vivo and post mortem - J. Lebenberg; M. Labit; G. Auzias; H. Mohlberg; C. Fischer; D. Rivière; E. Duchesnay; C. Kabdebon; F. Leroy; N. Labra; F. Poupon; T. Dickscheid; et al. (Brain Structure and Function, 2018)

The relative role of ecological interactions and environmental variables on the population dynamics of marine benthic polychaetes - Fabio A. Labra; Rodrigo A. Moreno; Sergio A. Alvarado; Franklin D. Carrasco; Sergio A. Estay; Marcelo M. Rivadeneira (Marine Biodiversity, 2018)

Identifying population thresholds for flowering plant reproductive success: the marsh gentian (Gentiana pneumonanthe) as a flagship species of humid meadows and heathland - Simon Pierce; Alberto Spada; Elisabetta Caporali; Filippa Puglisi; Andrea Panzeri; Alessandra Luzzaro; Simona Cislaghi; Lia Mantegazza; Elisa Cardarelli; Massimo Labra; Andrea Galimberti; Roberta M. Ceriani (Biodiversity and Conservation, 2018)

Advancement of spring arrival in a long-term study of a passerine bird: sex, age and environmental effects - Luis Cadahía; Antonieta Labra; Endre Knudsen; Anna Nilsson; Helene M. Lampe; Tore Slagsvold; Nils Chr. Stenseth (Oecologia, 2017)

Blood toxic metals and hemoglobin levels in Mexican children - Guadalupe López-Rodríguez; Marcos Galván; Marco González-Unzaga; Juan Hernández Ávila; M. Pérez-Labra (Environmental Monitoring and Assessment, 2017)

Life With or Without Names - M. Casiraghi; A. Galimberti; A. Sandionigi; A. Bruno; M. Labra (Evolutionary Biology, 2016)

Evaluating the efficacy of restoration plantings through DNA barcoding of frugivorous bird diets - A. Galimberti; S. Spinelli; A. Bruno; V. Mezzasalma; F. De Mattia; P. Cortis; M. Labra (Conservation Biology, 2016)
Frugivores are critical components of restoration programs because they are seed dispersers. Thus, knowledge about bird–plant trophic relationships is essential in the evaluation of the efficacy of restoration processes. Traditionally, the diet of frugivores is characterized by microscopically identifying plant residues in droppings, which is time‐consuming, requires botanical knowledge, and cannot be used for fragments lacking detectable morphological characteristics (e.g., fragmented seeds and skins). We examined whether DNA barcoding can be used as a universal tool to rapidly characterize the diet of a frugivorous bird, Eurasian blackcap ( Sylvia atricapilla ). We used the DNA barcoding results to assess restoration efforts and monitor the diversity of potentially dispersed plants in a protected area in northern Italy. We collected 642 Eurasian Blackcap droppings at the restored site during the autumn migration over 3 years. Intact seeds and fragmented plant material were analyzed at 2 plastidial barcode loci ( rbcL and trnH‐psbA ), and the resulting plant identifications were validated by comparison with a reference molecular data set of local flora. At least 17 plant species, including 7 of the 11 newly transplanted taxa, were found. Our results demonstrate the potential for DNA barcoding to be used to monitor the effectiveness of restoration plantings and to obtain information about fruit consumption and dispersal of invasive or unexpected plant species. Such an approach provides valuable information that could be used to study local plant biodiversity and to survey its evolution over time.

Genetic introgression of hybrid Rhododendron x intermedium Tausch is habitat mediated: Evidences from south-eastern Alps (Italy) - I. Bruni; F. De Mattia; S. Fluch; C. Ferrari; M. Corazza; E. Dinelli; M. Labra (Plant Biosystems, 2016)

Lamyropsis genus in the Mediterranean area: Phylogenetic position of L. microcephala (Asteraceae: Cardueae) - R. Gentili; G. Fenu; M. Labra; I. Bruni; E. Mattana; G. Bacchetta (Plant Biosystems, 2015)

A rapid diagnostic approach to identify poisonous plants using DNA barcoding data - S. Federici; D. Fontana; A. Galimberti; I. Bruni; F. De Mattia; P. Cortis; G. Galasso; M. Labra (Plant Biosystems, 2015)

Pea seed extracts stimulate germination of the terrestrial orchid Ophrys apifera Huds. during a habitat restoration project - Simon Pierce; Valentina Guidi; Andrea Ferrario; Roberta M. Ceriani; Massimo Labra; Ilda Vagge; Bruno E. L. Cerabolini (Plant Biosystems, 2015)

Analytical approaches for DNA barcoding data – how to find a way for plants? - A. Sandionigi; A. Galimberti; M. Labra; E. Ferri; E. Panunzi; F. De Mattia; M. Casiraghi (Plant Biosystems, 2012)

Allopatric divergence and secondary contacts in Euphorbia spinosa L: Influence of climatic changes on the split of the species - G. Zecca; G. Casazza; L. Minuto; M. Labra; F. Grassi (Organisms Diversity & Evolution, 2011)

Haplotype richness in refugial areas: phylogeographical structure of Saxifraga callosa - F. Grassi; L. Minuto; G. Casazza; M. Labra; F. Sala (Journal of Plant Research, 2009)

Chemical self-recognition in the lizard Liolaemus fitzgeraldi - Paz M. Aguilar; Antonieta Labra; Hermann M. Niemeyer (Journal of Ethology, 2009)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Phylogeographical structure and conservation genetics of wild grapevine - F. Grassi; M. Labra; S. Imazio; R. Ocete Rubio; O. Failla; A. Scienza; F. Sala (Conservation Genetics, 2006)

Chloroplast Microsatellites to Investigate the Origin of Grapevine - S. Imazio; M. Labra; F. Grassi; A. Scienza; O. Failla (Genetic Resources and Crop Evolution, 2006)

Molecular diversity in Ligurian local races of common bean ( Phaseolus vulgaris L.) - F. Grassi; M. Labra; L. Minuto (Plant Biosystems, 2006)

Genomic stability in Arabidopsis thaliana transgenic plants obtained by floral dip - M. Labra; C. Vannini; F. Grassi; M. Bracale; M. Balsemin; B. Basso; F. Sala (Theoretical and Applied Genetics, 2004)

Evidence of a secondary grapevine domestication centre detected by SSR analysis - F. Grassi; M. Labra; S. Imazio; A. Spada; S. Sgorbati; A. Scienza; F. Sala (Theoretical and Applied Genetics, 2003)

Age and Season Affect Chemical Discrimination of Liolaemus bellii Own Space - Antonieta Labra; Soledad Cortez; Hermann M. Niemeyer (Journal of Chemical Ecology, 2003)

A brief evolutionary excursion comes to an end: the genetic relationship of British species of Gentianella sect. Gentianella (Gentianaceae) - M. O. Winfield; P. J. Wilson; M. Labra; J. S. Parker (Plant Systematics and Evolution, 2003)

Chemical Composition of Precloacal Secretions of Two Liolaemus fabiani Populations: Are They Different? - Claudio M. Escobar; Carlos A. Escobar; Antonieta Labra; Hermann M. Niemeyer (Journal of Chemical Ecology, 2003)

Chemical Composition of Precloacal Secretions of Liolaemus Lizards - Carlos A. Escobar; Antonieta Labra; Hermann M. Niemeyer (Journal of Chemical Ecology, 2001)

Genomic changes in transgenic rice (Oryza sativa L.) plants produced by infecting calli with Agrobacterium tumefaciens - M. Labra; C. Savini; M. Bracale; N. Pelucchi; L. Colombo; M. Bardini; F. Sala (Plant Cell Reports, 2001)

The use of AFLP and SSR molecular markers to decipher homonyms and synonyms in grapevine cultivars: the case of the varietal group known as ’’Schiave’’ - T. Fossati; M. Labra; S. Castiglione; O. Failla; A. Scienza; F. Sala (Theoretical and Applied Genetics, 2001)

Intraspecific Chemical Recognition in the Lizard Liolaemus tenuis - Antonieta Labra; Hermann M. Niemeyer (Journal of Chemical Ecology, 1999)